PENGARUH METODE PEMASAKAN DAN TARAF PENAMBAHAN SERBUK BATA MERAH DAN ABU GOSOK TERHADAP KUALITAS ORGANOLEPTIK DAN KADAR AIR TELUR ASIN - Iwan Yulio Fendika (Universitas Islam Kadiri, 2019)
This study aims to determine the effect of cooking methods and the addition level of red brick and rub ash on organoleptic quality and salty egg moisture content.This research was conducted in Wonorejo Village, Pagerwojo Subdistrict, tulungagung Regency, which was held on February 16, 2018 to February 26, 2018, and the organoleptic test was conducted at the Islamic University of Kadiri Kediri which was held February 28, 2018 until March 7, 2018. grain with an average egg weight of 75 grams. The media used in making salted eggs are red brick, rub ash, salt and water. The research method was an experiment using Factorial Completely Randomized Design (CRD) that is with a factorial pattern 2 X 2 = 4 combinations of treatments consisting of 2 factors. The results of the discussion showed that the experiment of using red brick and scrub ash was very significant effect on the hedonic quality test of egg white color and also significantly affected the hedonic quality test of the aroma of salted eggs. The conclusion of this study shows that the administration of red brick and scrub ash gives a very real influence on color and gives a real influence on the aroma of salted eggs and based on the hedonic test shows that P2B2 treatment gives good results for panelists' preferences and moisture content. Suggestions from this study need further research to determine the more significant effect on hedonic quality testing and preferably on making salted eggs using cooking methods by steaming and using red brick powder media because it can give good results on consumer preferences and more moisture content reduced.